Composite negative electrode material, its preparation method and its application

The composite negative electrode material, featuring a porous carbon core, silicon particles, and a controlled pore structure, addresses the poor cycling performance of silicon-based anode materials by reducing volume expansion and stabilizing the SEI, resulting in improved capacity retention and structural stability.

JP2025512505AActive Publication Date: 2025-04-17BTR NEW MATERIAL GRP CO LTD +1

Patent Information

Application Number
JP2024560763
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-09-22
Filing Date
2023-09-14
Publication Date
2025-04-17
Estimated Expiration
2043-09-14

AI Technical Summary

Technical Problem

Conventional silicon-based anode materials for lithium-ion batteries suffer from poor cycling performance due to volume expansion, powdering, and instability of the solid electrolyte interface (SEI).

Method used

A composite negative electrode material is developed, comprising a core of porous carbon and silicon particles, with a coating layer on the surface. The silicon particles are distributed within the surface and/or pores of the porous carbon, creating a structure with a controlled ratio of micropores to mesopores, which enhances stability and reduces volume expansion.

Benefits of technology

The composite negative electrode material exhibits improved cycle performance, reduced volume expansion, and enhanced stability of the SEI, leading to better retention of capacity and reduced thickness expansion of the electrode sheet over multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512505000001_ABST
    Figure 2025512505000001_ABST
Patent Text Reader

Abstract

The composite negative electrode material and its preparation method and application belong to the field of battery technology. A composite negative electrode material comprising a core containing a porous carbon material and Si particles, and a coating layer located on at least a part of the surface of the core, the Si particles being distributed on the surface and / or in the pores of the porous carbon material, the composite negative electrode material comprising micropores and mesopores, the ratio of the pore volume of the micropores to the pore volume of the mesopores being 2:98 to 50:50, the oil absorption value of the composite negative electrode material being smaller than that of the composite negative electrode material after the Si particles have been removed, and the difference value when the oil absorption value of the composite negative electrode material after the Si particles have been removed is taken as 100% is ≧10%. In the composite negative electrode material, the porous properties of the porous carbon provide a space for the volume expansion of Si, and the use of porous carbon having a certain strength as a skeleton further ensures the stability of the entire composite negative electrode material, and improves the cycle performance of the composite negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to a Chinese patent application bearing application number "2022111553065" and title "Composite negative electrode material and its preparation method and application" filed with the China Patent Office on September 22, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to the field of battery technology, in particular to a composite negative electrode material and its preparation method and application. [Background technology]

[0003] Lithium ion batteries have the advantages of high energy density, long cycle life, little environmental pollution, no memory effect, etc., and are therefore widely used in electric vehicles and consumer electronics products. Conventional negative electrode carbon materials have limited widespread use due to their low theoretical specific capacity (372 mAh / g). In order to increase the energy density of lithium-ion batteries, high-capacity anode materials have begun to be sought, and silicon-based anode materials have become an increasingly hot research spot because of their theoretical specific capacity of 4200mAh / g. However, silicon-based negative electrode materials undergo rapid volume expansion during the process of alloying with lithium, and as the cycles progress, decay mechanisms occur, such as powdering, loss due to contact with the conductive agent and current collector, and formation of an unstable solid electrolyte interface (SEI), resulting in poor cycle performance for silicon-based negative electrode materials. Summary of the Invention [Problem to be solved by the invention]

[0004] Based on this, there is a need to provide a composite negative electrode material that can improve the cycle performance of a battery, as well as its preparation method and application. [Means for solving the problem]

[0005] In order to achieve the above object, the present application employs the following means.

[0006] One aspect of the present application provides a composite negative electrode material comprising a core containing a porous carbon material and Si (silicon) particles, and a coating layer located on at least a portion of a surface of the core, wherein the Si (silicon) particles are distributed on the surface and / or within the pores of the porous carbon material. The composite negative electrode material has micropores and mesopores, and a ratio of a pore volume of the micropores to a pore volume of the mesopores is from 2:98 to 50:50. The oil absorption value of the composite negative electrode material is smaller than the oil absorption value of the composite negative electrode material after the Si particles have been removed, and the difference between the oil absorption value of the composite negative electrode material after the Si particles have been removed is ≧10%, assuming that the oil absorption value of the composite negative electrode material is 100%.

[0007] In one embodiment, in the FIB-TEM test of the composite anode material, the EDS scan line density is 0.90≦(A 1 -C 1 ) / (C 1 -B 1 )≦1.10 and |((A 1 -B 1 ) / 2C 1 )2-1|≦0.01 (where A 1 is the maximum value along the scan line concentration of Si, B 1 is the minimum value along the scan line concentration of Si, C 1 is the median value along the scan line concentration of Si).

[0008] In one embodiment, in a FIB-TEM test of the composite anode material, the EDS scan line density is 0.90≦(A 2 -C 2 ) / (C 2 -B 2 ) ≦1.10 and |((A 2 -B 2 ) / 2C 2 ) 2 -1|≦0.01 (where A 2 C is the maximum value along the scan line density, B is the 2 is the minimum value along the C scan line density, C 2 is the median value along the C scan line density).

[0009] In one embodiment, the composite negative electrode material 29 In the Si-NMR spectrum, there is a Si-C resonance peak between -10 ppm and 20 ppm, and its intensity is D 1 It has a Si resonance peak between -90 ppm and -110 ppm, and its intensity is D 2 And D 2 / D 1 ≧10.

[0010] In one embodiment, the composite anode material includes amorphous Si-C bonds.

[0011] In one embodiment, the composite anode material has an X-ray diffraction pattern that includes a SiC crystalline peak.

[0012] In one embodiment, the porosity of the composite negative electrode material is 10% to 20%.

[0013] In one embodiment, when the composite negative electrode material is lithiated to 50% of its theoretical lithiation capacity, the porosity A1 of the electrode sheet including the composite negative electrode material is A1≧30%.

[0014] In one embodiment, when the composite negative electrode material is lithiated to 70% of its theoretical lithiation capacity, the porosity A2 of the electrode sheet including the composite negative electrode material is 20%≦A2<30%.

[0015] In one embodiment, when the composite negative electrode material is lithiated to 80% of its theoretical lithiation capacity, the porosity A3 of the electrode sheet including the composite negative electrode material is 10%≦A3≧20%.

[0016] In one embodiment, the ratio of the pore volume of the micropores to the pore volume of the mesopores is from 5:95 to 23:77.

[0017] In one embodiment, the average pore size of the closed pores of the composite negative electrode material after complete lithium intercalation is 0-10 nm.

[0018] In one embodiment, the mass percentage of Si in the composite negative electrode material is 10% to 90%, preferably 20% to 80%.

[0019] In one embodiment, the specific surface area of ​​the composite negative electrode material is 0.5 m 2 / g~50m 2 / g.

[0020] In one embodiment, the composite anode material has a true density of 1.80 g / cm 3 ~2.90g / cm 3 It is.

[0021] In one embodiment, the average particle size D of the composite negative electrode material 50 The thickness is 1 μm to 25 μm, preferably 2 μm to 15 μm, and more preferably 3 μm to 10 μm.

[0022] In one embodiment, the coating layer has an average thickness of 1 nm to 100 nm.

[0023] In one embodiment, the coating layer comprises a carbon coating layer.

[0024] In one embodiment, the average pore size of the porous carbon is R1, and the value of R1 is in the range of 0.2 nm to 1000 nm, preferably 2 nm to 500 nm.

[0025] In one embodiment, the ratio of the pore volume of the porous carbon having a diameter of 2 nm to 100 nm to the total pore volume is 50% or more.

[0026] In one embodiment, the ratio of the pore volume of the micropores to the pore volume of the mesopores in the porous carbon is from 95:5 to 50:50.

[0027] In one embodiment, the average distance between the pores of the porous carbon is H1, and the value of H1 ranges from 1 nm to 500 nm, preferably from 1 nm to 100 nm.

[0028] In one embodiment, the average distance H1 between the pores of the porous carbon≦the average pore diameter R1 of the porous carbon.

[0029] In one embodiment, the particle size of the porous carbon is 1 μm to 50 μm, and preferably 2 μm to 20 μm.

[0030] In one embodiment, the Si particles in the composite negative electrode material contain amorphous silicon and have a particle size in the range of 1 to 110 nm.

[0031] In one embodiment, the average particle size D of the Si particles in the composite negative electrode material 50 The thickness is from 1 nm to 200 nm, preferably from 2 nm to 100 nm, and more preferably from 5 nm to 50 nm.

[0032] In one embodiment, the Si crystal grains of the composite negative electrode material have a grain size of 2 nm to 10 nm, with a standard deviation σ≦0.2.

[0033] Another aspect of the present application provides a method for preparing the above composite negative electrode material. The preparation method includes the following steps: Depositing Si particles on the surface and / or pores of the porous carbon by a chemical vapor infiltration process (CVI) to obtain a precursor; and coating the precursor in a protective atmosphere to form a coating layer on the surface of the precursor to obtain a composite negative electrode material; the composite negative electrode material comprises micropores and mesopores, and the ratio of the pore volume of the micropores to the pore volume of the mesopores is from 2:98 to 50:50; The oil absorption value of the composite negative electrode material is smaller than the oil absorption value of the composite negative electrode material after the Si particles have been removed, and the difference therebetween is ≧10% when the oil absorption value of the composite negative electrode material after the Si particles have been removed is taken as 100%.

[0034] In one embodiment, the step of depositing Si particles on the surface and / or in the pores of the porous carbon using the chemical vapor infiltration process includes providing porous carbon, flowing a reactant gas, and pyrolyzing the reactant gas to deposit Si particles on the surface and / or in the pores of the porous carbon.

[0035] In one embodiment, the reaction gas includes a gaseous Si source, hydrogen gas, and an inert gas.

[0036] In one embodiment, the pyrolysis temperature is 300°C to 500°C;

[0037] In one embodiment, the pyrolysis time is 0.2 h to 20 h.

[0038] In one embodiment, the flow rate of the reaction gas is 50 L / min to 200 L / min.

[0039] In one embodiment, the reaction gas comprises a gaseous Si source, and the raw material of the gaseous Si source includes at least one of monosilane, disilane, monochlorosilane, dichlorosilane, trichlorosilane, and tetrachlorosilane.

[0040] In one embodiment, the reactive gas comprises an inert gas, the inert gas including at least one of nitrogen gas, helium gas, neon gas, and argon gas.

[0041] In one embodiment, the reaction gas comprises an inert gas, and the flow rate of the inert gas is between 0.2 L / min and 50 L / min.

[0042] In one embodiment, the flow ratio of the gaseous Si source to the inert gas is 1:1-20.

[0043] In one embodiment, the method for producing the porous carbon includes the steps of pyrolyzing an organic carbon source and chemically activating the organic carbon source.

[0044] In one embodiment, the coating process includes mixing a precursor with a carbon source and controlling the pyrolysis of the carbon source in a protective atmosphere to form a carbon coating layer on the surface of the precursor.

[0045] In one embodiment, the carbon coating layer is formed in a manner including at least one of a gas phase carbon coating process, a solid phase carbon coating process, and a liquid phase carbon coating process.

[0046] In one embodiment, the inert gas includes at least one of nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas.

[0047] In one embodiment, the gas flow rate of the protective atmosphere is 20 mL / min to 1000 mL / min.

[0048] In one embodiment, the carbon source comprises a gas phase carbon source.

[0049] In one embodiment, the carbon source comprises a gas phase carbon source, the gas phase carbon source comprising a gas phase hydrocarbon-based carbon source.

[0050] In one embodiment, the carbon source comprises a gas phase carbon source, the gas phase carbon source comprising at least one of methane, acetylene, ethylene, ethane, propane, propylene, propyne, acetone, and benzene.

[0051] In one embodiment, the carbon source comprises a solid phase carbon source.

[0052] In one embodiment, the carbon source comprises a solid phase carbon source, the solid phase carbon source comprises a solid phase organic carbon source.

[0053] In one embodiment, the carbon source comprises a solid phase carbon source, the solid phase carbon source comprising at least one of citric acid, glucose, pitch, phenolic resin, and furfural resin.

[0054] In one embodiment, the carbon source comprises a liquid phase carbon source.

[0055] In one embodiment, the carbon source comprises a liquid phase carbon source, the liquid phase carbon source comprises a liquid phase organic carbon source.

[0056] In one embodiment, the carbon source comprises a liquid phase carbon source, the liquid phase carbon source comprising at least one of n-hexane, toluene, benzene, xylene, methanol, ethanol, propanol, butanol, pentanol, acetone, butanone, 2-pentanone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and pentyl acetate.

[0057] In one embodiment, the pyrolysis temperature is 600°C to 1200°C.

[0058] In one embodiment, the temperature rise rate of the pyrolysis is 0.1° C. / min to 50° C. / min.

[0059] In one embodiment, the total pressure of the reaction system by the reaction gas is 100 kPa to 2000 kPa.

[0060] In one embodiment, the total pressure of the reaction system by the reaction gas is 100 kPa to 2000 kPa, and the partial pressure of the gaseous Si source is 1 kPa to 100 kPa.

[0061] In one embodiment, the total pressure of the reaction system due to the reaction gas is 100 kPa to 2000 kPa, and the partial pressure of the hydrogen gas is 50 kPa to 1000 kPa.

[0062] In one embodiment, the total pressure of the reaction system by the reaction gas is 100 kPa to 2000 kPa, and the partial pressure of the inert gas is 1 kPa to 1000 kPa.

[0063] Another aspect of the present application provides a negative electrode sheet comprising the above-mentioned composite negative electrode material or a composite negative electrode material prepared by the above-mentioned preparation method.

[0064] Yet another aspect of the present application further provides a battery including the above negative electrode sheet.

[0065] Yet another aspect of the present application provides an electrical device comprising the battery described above. Effect of the Invention

[0066] The above composite negative electrode material and its preparation method have at least the following advantages over the prior art:

[0067] (1) The above composite negative electrode material maintains the advantage of Si having a large specific capacity as a negative electrode, while utilizing the porous properties of the porous carbon to provide space for the volumetric expansion of Si. By providing space for the volumetric expansion of Si, the volumetric expansion of the material is further reduced. By having a coating layer of a certain strength on the surface of the core, it is also possible to cover the Si particles exposed on the surface of the core, thereby reducing direct contact between the Si particles and the electrolyte and forming a thin SEI film when the negative electrode material comes into contact with the electrolyte, resulting in less wear on the electrolyte and better cycle retention. By rationally controlling the volume ratio of micropores and mesopores in the composite negative electrode material, the oil absorption value of the composite negative electrode material after filling with Si particles is made smaller than that of the composite negative electrode material after removing the Si particles, which indicates that some of the pores in the composite negative electrode material are effectively filled and the side reaction between the composite negative electrode material and the electrolyte can be reduced, and the volume expansion of Si can be alleviated during the charge and discharge cycles, and the stability of the entire material can be maintained and the structure of the material cannot be collapsed during the cycles, thereby improving the cycle performance of the material.

[0068] (2) The composite anode material produced by CVI (Chemical Vapor Infiltration) technology has mainly amorphous Si particles, which makes it possible to avoid problems such as the anisotropic expansion of crystalline S during the lithium insertion process, which leads to the collapse of the pore structure, rapid decay of the specific capacity, and poor cycle performance when lithium is inserted. The Si particles can be well dispersed in the pores and skeleton of the porous carbon and are intercalated in the carbon skeleton at the atomic level, so that the coating layer on the porous carbon skeleton is complete and strong, improving the compatibility issue between nano-Si and the electrolyte, which is favorable for the formation of a stable SEI film. [Brief description of the drawings]

[0069] [Figure 1] FIG. 1 is a structural schematic diagram of a composite anode material according to an embodiment of the present application, in which: 1—coating layer; 2—porous carbon material; 3—Si particles; 4—mesopores; 5—micropores. [Diagram 2] FIG. 2 is a schematic diagram showing the relationship between the average distance between pores of a porous carbon and the average pore size of the porous carbon according to an embodiment of the present application. [Diagram 3] 4 is a flow chart of a method for preparing a composite negative electrode material according to another embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0070] In order to make the inventive objectives, technical solutions and advantages of the present application more clear, the present application will be further described in detail in the following in combination with examples. The specific embodiments described herein are merely illustrative of the present application and are not intended to be limitations of the present application.

[0071] All technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs, unless otherwise defined. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the present application. As used herein, the term "and / or" includes any and all combinations of one or more of the associated items.

[0072] In this application, technical features described in an open-ended manner include closed-ended inventions consisting of the recited features, and also include open-ended inventions comprising the recited features.

[0073] Referring to FIG. 1 , in one embodiment of the present application, a composite negative electrode material is provided that includes a core containing a porous carbon material 2 and Si particles 3, and a coating layer 1 located on at least a part of a surface of the core, and the Si particles 3 are distributed on the surface and / or in the pores of the porous carbon material 2.

[0074] The composite negative electrode material has micropores 5 and mesopores 4, and the ratio of the pore volume of the micropores 5 to the pore volume of the mesopores 4 is (2-50):(50-98).

[0075] The oil absorption value of the above composite negative electrode material is smaller than the oil absorption value of the composite negative electrode material after the Si particles are removed, and when the oil absorption value of the composite negative electrode material after the Si particles are removed is taken as 100%, the difference therebetween is ≧10%.

[0076] In this embodiment, the negative electrode material comprises a core and a coating layer located on the surface thereof, the Si particles in the core are located on the surface and / or in the pores of the porous carbon material, and the porous carbon material supports the Si particles as a framework, and the porous characteristic thereof reduces the volume expansion of the material by providing space for the Si to expand in the process of lithium desorption and insertion. The core surface has a coating layer with a certain strength so that the core is mechanically restrained, which relieves the volume expansion stress of the core and covers the Si particles exposed on the core surface, reducing direct contact between the Si particles and the electrolyte while not affecting lithium ion transport, and forming a thin SEI film when the negative electrode material comes into contact with the electrolyte, which is advantageous for reducing consumption by the electrolyte and improving the cycle retention rate. It can also improve the capacity of the material, and the presence of the coating layer further improves the structural stability of the entire composite negative electrode material. Before bonding with the Si particles, the micropores of the porous carbon are mainly fine pores, and after the preparation of the composite negative electrode material is completed, most of the micropores are filled with Si particles, and the remaining pores of the porous carbon are mainly closed mesopores distributed inside the unfilled particles. By controlling the volume ratio of micropores and mesopores in the negative electrode material, the oil absorption value of the composite negative electrode material after filling with Si particles can be made smaller than that of the composite negative electrode material after removing the Si particles, which indicates that some of the pores in the composite negative electrode material can be effectively filled and side reactions between the composite negative electrode material and the electrolyte can be reduced. Furthermore, it is possible to adjust the filling degree of the Si particles, improve the specific capacity of the material, and alleviate the volumetric expansion of Si. In addition, the stability of the entire material is maintained and the structure of the material does not collapse during cycling, so that the cycle performance, electrochemical performance, etc. of the material are improved by the synergistic effect of the above-mentioned overall structure.

[0077] In the prior art, the cycle characteristics of Si-based composite negative electrode materials were improved by using a method of recombining porous carbon materials with Si. However, the manufactured Si-based composite negative electrode materials could not achieve a balance between performance such as the initial discharge specific capacity, the initial coulombic efficiency, the capacity retention rate after cycling, and the expansion rate of the electrode sheet thickness after cycling. For example, the conventional Si-based composite negative electrode materials had a battery capacity retention rate of about 85% after 50 cycles, but the initial discharge specific capacity and the initial coulombic efficiency were low, the expansion rate of the electrode sheet thickness after cycling was high, and the structure was easily destroyed during cycling. Therefore, the overall performance of Si-based composite negative electrode materials still needs to be improved. In response to this, the applicant has made creative improvements and conducted experiments and verified that the above problem can be solved by controlling the ratio of the pore volume of micropores to the pore volume of mesopores in the composite negative electrode material.

[0078] In this embodiment, the ratio of the pore volume of the micropores to the pore volume of the mesopores in the composite negative electrode material is controlled to (2-50):(50-98), thereby improving the initial discharge specific capacity, the initial coulombic efficiency, and the capacity retention rate after cycling of the battery, and also reducing the thickness expansion rate of the electrode sheet after cycling. Furthermore, if the pore volume ratio of micropores in the composite negative electrode material is too large, there will not be enough pores to withstand the volume expansion during charge and discharge. In reality, due to factors such as diffusion limitations, 100% of the pores in the porous carbon may not be filled with Si. If the pore volume ratio of mesopores in the composite negative electrode material is too large, the amount of Si filled will be too small, resulting in a decrease in specific capacity. Meanwhile, since there are still many voids, the overall structure of the composite negative electrode material is not stable and is prone to collapse during cycling. In addition, the pores on the surface of the porous carbon material are filled with silicon to form micropores. However, most of the mesopores are located inside the porous carbon material or are in a closed state, making it difficult to fill them efficiently. Therefore, in the actual filling process, mainly the micropores are filled, and the composite negative electrode material after deposition has a higher occupancy rate of mesopores.

[0079] In one embodiment, the ratio of the pore volume of the micropores to the pore volume of the mesopores in the composite negative electrode material may be, for example and without limitation, 2:98, 5:95, 10:90, 20:80, 24:76, 28:72, 30:70, 38:62, 40:60, 45:55, or 50:50, or other values ​​within this range. The ratio of the pore volume of the micropores to the pore volume of the mesopores in the composite negative electrode material is preferably (5-23):(77-95).

[0080] In one embodiment, the oil absorption value of the composite negative electrode material is less than the oil absorption value of the composite negative electrode material after removing the Si particles, and the difference is ≧10%.

[0081] It is understood that the Si particles distributed on the surface and / or in the pores of the porous carbon material reduce the pores of the porous carbon in the composite negative electrode material, thereby decreasing the oil absorption value of the composite negative electrode material. The oil absorption value of the composite negative electrode material is smaller than the oil absorption value of the composite negative electrode material after the Si particles are removed, and the difference value can be, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30% or 40% (the oil absorption value of the composite negative electrode material after the Si particles are removed is taken as 100%). Naturally, the difference between the oil absorption value of the composite negative electrode material and the oil absorption value of the composite negative electrode material after the Si particles are removed should not reach 100%, and should not be too high either. This is because a certain number of pores must be left in the porous carbon material to alleviate the expansion of the Si volume when lithium is inserted. It can be seen that if the difference value is less than 10%, the composite negative electrode material has too many pores, which reduces the strength and structural stability of the composite negative electrode material, making the material structure more likely to collapse during cycling and reducing the material's cycle performance.

[0082] In one specific example, in a FIB-TEM (Focused Ion Beam-Transmission Electron Microscope) test of a composite anode material, the scanning line density of EDS (Energy Dispersive Spectroscopy) was 0.90≦(A 1 -C 1 ) / (C 1 -B 1 )≦1.10 and |((A 1 -B 1 ) / 2C 1 )2-1|≦0.01. Here, A 1 is the maximum value along the scan line concentration of Si, B 1 is the minimum value along the scan line concentration of Si, C 1 is the median value along the scan line concentration of Si. (A 1 -C 1 ) / (C 1 -B 1It is understood that ) may be any value between 0.90 and 1.10, such as 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.05, 1.07, 1.08, or 1.10. |((A 1 -B 1 ) / 2C 1 ) 2 -1| may be 0.0065, 0.0070, 0.0079, 0.008, 0.0088, 0.0089, 0.009, 0.0093, 0.0098 or 0.01, etc.

[0083] In one specific example, in a FIB-TEM test of a composite anode material, the EDS scan line concentration is: 0.90≦(A 2 -C 2 ) / (C 2 -B 2 )≦1.10, And |((A 2 -B 2 ) / 2C 2 ) 2 -1|≦0.01 This relationship is satisfied. Here, A 2 C is the maximum value along the scan line density, B is the 2 is the minimum value along the C scan line density, C 2 is the median value along the C scan line density. (A 2 -C 2 ) / (C 2 -B 2 ) may be any value between 0.90 and 1.10, for example, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.05, 1.08, or 1.10. |((A 2 -B 2 ) / 2C 2 ) 2-1| may be 0.0065, 0.0067, 0.0070, 0.0074, 0.0079, 0.008, 0.0088, 0.0089, 0.009, 0.0093, 0.0098, 0.01, etc.

[0084] The FIB-TEM test was carried out to measure the distribution of C and Si elements on the cut surface of the composite negative electrode material particles. Since the composite negative electrode material contains Si and C elements, the EDS scan lines are at least two, one for the Si element and one for the C element. When the Si scan line concentration and the C scan line concentration in the EDS satisfy the above relationship, nanosilicon is dispersed in the porous carbon material, and the porous carbon material can efficiently provide an expansion space for the Si particles distributed around it, thereby ensuring the structural stability of the composite negative electrode material during charging and discharging.

[0085] In one embodiment, the composite anode material 29 In the Si-NMR spectrum, there is a Si-C resonance peak between -10 ppm and 20 ppm, and its intensity is D 1 It has a Si resonance peak between -90 ppm and -110 ppm, and its intensity is D 2 And D 2 / D 1 ≧10.

[0086] It should be noted that a trace amount of SiC is present in the composite negative electrode material of this embodiment. Since SiC is an inactive material, the specific capacity decreases as the SiC content increases, and the D 2 / D 1 If it is ≧10, it explains that there is a certain bonding force between Si and C in the composite negative electrode material, and a bonding force at the atomic level occurs between Si and C. At the same time, since only a small amount of crystalline SiC is present, the composite anode material of the present invention can maintain structural stability during the charge and discharge process and exhibits excellent cycle performance. To help you understand, D 2 / D 1may be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 35, 40, or 50, etc., and is not limited thereto. D 2 / D 1 The higher the value, the lower the content of inert SiC.

[0087] In one embodiment, the composite anode material contains amorphous Si-C bonds, which are formed by bonding Si atoms with C atoms.

[0088] The SiC in the composite negative electrode material of this embodiment is basically in an amorphous state.

[0089] In one embodiment, the composite anode material contains trace amounts of SiC crystalline peaks in the X-ray diffraction pattern.

[0090] In addition, since a relatively high content of crystalline SiC leads to a decrease in the specific capacity of the composite negative electrode material, the SiC in the composite negative electrode material of this embodiment is mostly in an amorphous state, with only a trace amount of SiC being in a crystalline state.

[0091] In one embodiment, the porosity of the composite negative electrode material is between 10% and 20%. When the porosity is less than 10%, the composite negative electrode material does not have sufficient pores to withstand the volume expansion during charge and discharge, and Si particles precipitate on the surface and / or within the pores of the porous carbon due to factors such as diffusion restriction, making it impossible to fill the pores 100%. If the porosity of the composite negative electrode material is higher than 20%, the specific capacity will be low because the amount of Si filled is too small, while the overall stability of the negative electrode material will be poor due to the presence of a large number of pores in the composite negative electrode material, making it prone to collapse during cycling. The porosity of the composite anode material may be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%. The porosity of the composite negative electrode material may also be other values ​​between 10% and 20%.

[0092] As a specific example, when the composite negative electrode material is lithiated to 50% of its theoretical lithiation capacity, the porosity A1 of the electrode sheet containing the composite negative electrode material is A1≧30%, and further, when the composite negative electrode material is lithiated to 70% of its theoretical lithiation capacity, the porosity A2 of the electrode sheet containing the composite negative electrode material is 20%≦A2<30%. Furthermore, when the composite negative electrode material is lithiated to 80% of its theoretical lithiation capacity, the porosity A3 of the electrode sheet containing the composite negative electrode material is 10%≦A3<20. The "electrode sheet" refers to an electrode sheet that uses a composite negative electrode material as an active material and is made of one or more conductive agents, binders, and solvents commonly used in this technical field, such as the electrode sheets produced in the examples of this application. If the electrode sheet does not satisfy the above-mentioned conditions regarding porosity, it indicates that the composite negative electrode material does not have sufficient pore space to accommodate the volume expansion of Si when lithiated. Thus, when lithium is inserted, the expansion of Si brings about a large expansion stress on the surrounding porous carbon, destabilizing the structure of the composite negative electrode material and deteriorating the electrochemical performance. Furthermore, graphite material is also added to conventional electrode sheets, and if the porosity is outside the above range, the Si will press against the surrounding graphite sheet structure layers during its volume expansion, making the entire electrode sheet unstable.

[0093] In one embodiment, the average pore size of the closed pores of the composite negative electrode material after full lithium loading was 0-10 nm. By "fully intercalating lithium" it is meant that the composite negative electrode material is saturated with lithium ions. If the pore size of the closed pores in the porous carbon after lithium is completely inserted is larger than 10 nm, the pores in that partial region will be large, resulting in insufficient mechanical strength of the composite anode material, making it easy for stress weak points to appear, and the structure will break during the charge and discharge process, which may allow a large amount of electrolyte to seep in, which may be detrimental to the electrochemical performance of the composite anode material. Alternatively, the pore size of the closed pores in the porous carbon after the lithium is completely inserted may be 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, or 10 nm, or other values ​​between 0 and 10 nm.

[0094] In one specific example, the mass percentage of Si in the composite negative electrode material is 10% to 90%, and preferably 20% to 80%. It can be understood that the mass percentage of Si in the composite negative electrode material is 10%, 12%, 14%, 16%, 18%, 20%, 25%, 30%, 35%, 40%, 50%, 60%, 70%, 80% or 90%. The mass percentage of Si contained in the composite negative electrode material may be any other value between 10% and 90%.

[0095] In one embodiment, the specific surface area of ​​the composite anode material is 0.5 m 2 / g~50m 2 / g. The specific surface area of ​​the composite negative electrode material is 0.5 m 2 / g, 1.0m 2 / g, 5.0m 2 / g, 10m 2 / g, 13m 2 / g, 16m 2 / g, 20m 2 / g, 23m 2 / g, 26m 2 / g, 30m 2 / g, 33m 2 / g, 36m 2 / g, 40m 2 / g, 43m 2 / g, 46m 2 / g or 50m 2 / g. The specific surface area of ​​the composite negative electrode material is 0.5 m 2 / g~50m 2 / g may be used.

[0096] In one embodiment, the composite anode material has a true density of 1.80 g / cm 3 ~2.90g / cm 3 It is. The true density of the composite anode material is 1.80 g / cm 3 , 1.90g / cm 3 , 2.00g / cm 3 , 2.10g / cm 3 , 2.20g / cm 3 , 2.30g / cm 3 , 2.40g / cm 3 , 2.50g / cm 3 , 2.60g / cm 3 , 2.70g / cm 3 , 2.80g / cm 3 or 2.90 g / cm 3 may be also possible. The true density of the composite anode material is 1.80 g / cm 3 ~2.90g / cm 3 It may be any other value between .

[0097] In one embodiment, the average particle size D of the composite negative electrode material 50 The thickness is 1 μm to 25 μm, preferably 2 μm to 15 μm, and more preferably 3 μm to 10 μm. In addition, when the average particle size of the composite negative electrode material is 1 μm or more, the decrease in tap density of the electrode that affects the processability as a negative electrode of a lithium ion battery can be reduced, the problem of the tap density of the electrode sheet being too low resulting in low energy density can be avoided, and an appropriate volumetric capacity can be obtained. Furthermore, when the average particle size of the composite negative electrode material is 25 μm or less, the electrode forming slurry can be appropriately applied to a uniform thickness. Average particle size D of the composite negative electrode material 50 may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 15 μm, 17 μm, 19 μm, 21 μm, 23 μm, or 25 μm. Average particle size D of the composite negative electrode material 50 may be other values ​​between 1 μm and 25 μm.

[0098] In one embodiment, the average thickness of the coating layer is from 1 nm to 100 nm. It is understood that the average thickness of the coating layer is 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or 100 nm. The average thickness of the coating layer may be other values ​​between 1 nm and 100 nm.

[0099] In one specific example, the coating layer includes a carbon coating layer. It is understood that the carbon coating layer can mechanically restrain the core as a shale, allowing lithium ions to pass through but preventing interaction between the electrolyte and the internal active material, and that the C in the carbon coating layer can bond with the amorphous Si in the porous carbon to form amorphous Si-C bonds, thereby enhancing the interfacial bonding strength.

[0100] In one specific example, the average pore size of the porous carbon is R1, and the value of R1 ranges from 0.2 nm to 1000 nm, preferably from 2 nm to 500 nm. The pores of the porous carbon may be an open pore structure or a closed pore structure, and the internal pores of the porous carbon include closed pores that contribute to an increase in volume when lithium is inserted, but the stability of the silicon-carbon interface can be further improved without destroying the structure of the porous carbon or significantly increasing the size of the entire composite negative electrode material. The closed pores in porous carbon provide space to buffer the volume expansion of Si when lithium is inserted, while the absence of openings connecting to the outside world makes it difficult for the electrolyte to penetrate, eliminating the problem of the SEI layer continuing to thicken. The average pore size of the porous carbon is 0.2 nm, 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm or 1000 nm. The average pore size of the porous carbon may be other values ​​between 0.2 nm and 1000 nm.

[0101] In one specific example, the pore volume of the porous carbon is 50% or more of the pore volume having a size of 2 nm to 100 nm. It is understood that the volume ratio of pores of 2 nm to 100 nm in the pore volume of the porous carbon is, for example, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, or 75%.

[0102] In one specific example, the ratio of the pore volume of the micropores to the pore volume of the mesopores in the porous carbon is (50-95):(5-50).

[0103] Furthermore, if the pores in the porous carbon are larger than 100 nm, Si atoms can penetrate into the pores, but Si and the C in the porous carbon cannot be mixed uniformly at the nano level, and this leads to a deterioration of the electrochemical performance due to the uneven distribution of Si and C. When the porous carbon is in good contact with the gaseous silicon source, the gaseous silicon source is efficiently infiltrated into the inside of the porous carbon material, so that the micropores in the porous carbon are effectively filled, and the pores remaining in the composite negative electrode material are mainly mesopores that are distributed inside the particles and in a closed state. When the gaseous silicon source forms a shell on the surface of the porous carbon particles, the interior of the porous carbon is not efficiently filled with a large amount of micropores, and the pores remaining in the composite negative electrode material are mainly micropores. The ratio of the pore volume of the micropores to the pore volume of the mesopores in the porous carbon may be, for example, 95:5, 90:10, or 80:20, or it may be 70:30, 60:40, or 50:50, etc.

[0104] In one embodiment, the average distance between pores in the porous carbon is H1, and the value of H1 ranges from 1 nm to 500 nm, preferably from 1 nm to 100 nm. The average distance between pores in the porous carbon means the average value of the shortest distance between the edges of adjacent pores in the porous carbon, and the average distance between pores in the porous carbon may be 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 40 nm, 60 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, or may be another value between 1 nm and 500 nm.

[0105] As a specific example, refer to FIG. 2, which shows the relationship between the average spacing H1 between the pores of the porous carbon and the average pore diameter R1 of the porous carbon, where the average spacing H1 between the pores of the porous carbon is less than or equal to the average pore diameter R1 of the porous carbon, where H1 is the distance from the outer edge of one pore to the outer edge of an adjacent pore. It has been explained that when the average distance H1 between pores in the porous carbon is less than or equal to the average pore diameter R1 of the porous carbon, the distribution of pores in the porous carbon, i.e., the pores in the porous carbon, are relatively developed.

[0106] In one specific example, the particle size of the porous carbon is 1 μm to 50 μm, and preferably 2 μm to 20 μm. It is understood that the particle size of the porous carbon is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 17 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm. The particle size of the porous carbon may be other values ​​between 1 μm and 50 μm.

[0107] In a specific example, the Si particles in the composite negative electrode material contain amorphous silicon and have a particle size in the range of 1 to 110 nm.

[0108] The Si in the core of the composite negative electrode material is mainly amorphous, and the amorphous Si serves as the negative electrode to receive lithium ions that have migrated from the positive electrode and store energy. When the Si in the core of the composite negative electrode material is amorphous, it can bond with the C in the coating layer to form amorphous Si-C bonds to increase the interfacial bonding strength. The particle size of the Si particles is 1 nm, 3 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm or 110 nm. The particle size of the Si particles may be other values ​​between 1 nm and 110 nm.

[0109] In one specific example, the average particle size of the Si particles in the composite negative electrode material is 1 nm to 200 nm, preferably 2 nm to 100 nm, and more preferably 5 nm to 50 nm. When the average particle size of the Si particles is 1 nm or more, the Si particles are prevented from passing through the pores of the core and becoming detached. Furthermore, when the average particle size of the Si particles is 200 nm or less, the holes and small Si particles contained in the core can effectively suppress pulverization due to volume expansion of Si during charge and discharge processes, improving the cycle performance of the material. The distribution of Si particles in the porous carbon is determined by the CVI process, and depends mainly on the flow rates, partial pressures and ratios of the Si source gas, hydrogen gas and inert gas. The average particle size of the Si particles in the composite negative electrode material may be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm or 200 nm. The average particle size of the Si particles in the composite negative electrode material may be other values ​​between 1 nm and 200 nm.

[0110] In one specific example, the Si crystal grains of the composite negative electrode material have a grain size of 2 nm to 10 nm with a standard deviation σ≦0.2. The grain size of the Si crystal grains in the composite anode material may be 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm or 10 nm. The grain size of the Si crystal grains in the composite negative electrode material may be other values ​​between 2 nm and 10 nm.

[0111] Conventional Si / C composite anode materials can be synthesized by heating and vaporizing a Si-based material, followed by mixing and precipitating it. However, this method requires a high-temperature process at 1600° C. or higher, which increases the process cost, and most of the silicon prepared by this method is crystalline silicon. The expansion and contraction of crystalline silicon during charging and discharging is closely related to the orientation of its crystal grains, so expansion anisotropy is likely to occur during cycling, which is disadvantageous in terms of maintaining the integrity of the structure.

[0112] Conventional Si / C composite anode materials can also be prepared by calcining hydrogen silsesquioxane (abbreviated as HSQ) and a carbon precursor. The HSQ used in this method is expensive, and this method is limited to the initial precursor of HSQ, but it can only synthesize silicon oxide with an uncontrollable silicon-oxygen ratio, and can only synthesize SiO x The specific capacitance and initial coulombic efficiency of the material were much lower than those of the pure Si material.

[0113] In the prior art, a precursor solution containing a Si-based material source, a carbon source and a catalyst material is sprayed and pyrolyzed to form pores, and the by-products are removed to prepare a porous Si / C composite anode material. Although this combines the advantages of a porous structure and a Si-based material, the catalyst used in this method is an alkaline solution, and even if the catalyst is subsequently removed with water, an acid or an alkaline solution, it cannot be completely removed. While it causes serious environmental pollution, residual alkaline solution can cause high pH, ​​which poses the risk of gas generation during subsequent slurry preparation and charging / discharging cycles.

[0114] Conventional techniques also include mixing activated carbon powder with nano-Si slurry and coal tar asphalt, subjecting the mixture to coking and low-temperature carbonization, and then pulverizing and classifying the mixture to prepare a Si / C composite negative electrode material. In this method, it is not possible to control the type and size of the pores between the carbon material and the nano-Si particles after filling with Si particles, and it is also not possible to form Si-C bonds at the interface, resulting in insufficient connection strength between Si and C.

[0115] To address the above problems, referring to FIG. 3, one embodiment of the present application provides a method for preparing a composite negative electrode material, including the following steps:

[0116] Step S100 obtains a precursor by depositing Si particles on the surface and / or pores of the porous carbon by a chemical vapor infiltration process (CVI).

[0117] Step S200 involves coating the precursor in a protective atmosphere to form a coating layer on the surface of the precursor to obtain a composite negative electrode material.

[0118] Here, the composite negative electrode material has micropores and mesopores, and the ratio of the pore volume of the micropores to the pore volume of the mesopores is (2-50):(50-98).

[0119] The oil absorption value of the above composite negative electrode material is smaller than the oil absorption value of the composite negative electrode material after the Si particles have been removed, and the difference therebetween is ≧10% when the oil absorption value of the composite negative electrode material after the Si particles have been removed is taken as 100%. The Si particles produced by the CVI technique in this embodiment are mainly in an amorphous state, and therefore, it is possible to avoid problems that occur when crystalline S expands anisotropically during the lithium insertion process, causing the collapse of the pore structure, rapid decay of the specific capacity, and poor cycle performance when lithium is inserted. In addition, Si atoms are embedded in the carbon skeleton at the atomic level, and the coating layer that coats the porous carbon material skeleton can be made complete and strong, improving the compatibility between nano-Si and the electrolyte, which is advantageous for the formation of a stable SEI film. In the process of lithium insertion, the amorphous silicon of this embodiment expands isotropically, mitigating the change in volume, which is advantageous in solving the problem of amorphous silicon particles being powdered and falling off from the electrode. In this embodiment, the ratio of the pore volume of the micropores to the pore volume of the mesopores in the composite negative electrode material is controlled to be (2~50):(50~98), and may be, for example, 2:98, 5:95, 10:90, 20:80, 24:76, 28:72, 30:70, 34:66, 38:62, 40:60, 45:55, or 50:50, etc. This is because, when the ratio of the pore volume of the micropores is relatively large, the composite negative electrode material does not have enough pores to withstand the volume expansion during the charge and discharge process, and when the pore volume of the mesopores is relatively large, the specific capacity is low due to the filling of too little Si, while the composite negative electrode material still has many pores, so the stability of the overall structure is poor and it is easy to collapse during cycling.

[0120] Step S100 deposits Si particles on the surface and / or pores of the porous carbon by a chemical vapor infiltration process (CVI) to obtain a precursor.

[0121] As a specific example, the step of depositing Si particles on the surface and / or pores of porous carbon by a chemical vapor infiltration process includes providing porous carbon, flowing in a reactant gas, and pyrolyzing the reactant gas to deposit Si particles on the surface and / or in the pores of the porous carbon.

[0122] Alternatively, the chemical vapor infiltration process (CVI) is carried out in a CVI furnace, which includes a gas preheat zone for preheating the reactant gases and a reactor for preparing the precursors.

[0123] Specifically, the pyrolysis temperature is 300°C to 500°C. The temperature of pyrolysis may be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 390°C, 400°C, 430°C, 460°C, 490°C or 500°C. The pyrolysis temperature may also be other values ​​between 300°C and 500°C.

[0124] Specifically, the pyrolysis time is 0.2 to 20 hours. The time for pyrolysis may be 0.2h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h. The pyrolysis time may be other values ​​between 0.2 h and 20 h.

[0125] Specifically, the flow rate of the reaction gas is 50 L / min to 200 L / min. The flow rate of the reactant gas may be 50 L / min, 60 L / min, 70 L / min, 80 L / min, 90 L / min, 100 L / min, 110 L / min, 120 L / min, 130 L / min, 140 L / min, 150 L / min, 160 L / min, 170 L / min, 180 L / min, 190 L / min, or 200 L / min. The flow rate of the reaction gas may be other values ​​between 50 L / min and 200 L / min.

[0126] As a specific example, the method for preparing porous carbon includes a step of pyrolyzing an organic carbon source and a step of activating the organic carbon source, and the activation treatment may be at least one of a physical activation treatment and / or a chemical activation treatment.

[0127] The chemical activation treatment is a process in which a carbon material is activated with an activated pore-forming agent to form pores. These are mainly micropores generated during the above-mentioned activation process to form pores. However, excessive activation causes the pore walls of the micropores to collapse, resulting in the formation of mesopores and macropores in the carbon material. As a result, most of the mesopores are distributed inside the carbon material particles, and there is a high probability that they will become closed pores.

[0128] As a specific example, the reaction gas includes a gaseous Si source, hydrogen gas, and an inert gas.

[0129] In one specific example, the total pressure of the reaction system due to the reaction gas is 100 kPa to 2000 kPa. Specifically, the total pressure of the reaction system may be 100 kPa, 120 kPa, 150 kPa, 180 kPa, 200 kPa, 300 kPa, 400 kPa, 500 kPa, 600 kPa, 700 kPa, 800 kPa, 1000 kPa, 1200 kPa, 1400 kPa, 1600 kPa, 1800 kPa, or 2000 kPa, or may be another value between 100 kPa and 2000 kPa.

[0130] Specifically, the partial pressure of the gaseous Si source is 1 kPa to 100 kPa. For example, the partial pressure of the gaseous Si source may be 1 kPa, 2 kPa, 5 kPa, 7 kPa, 10 kPa, 15 kPa, 20 kPa, 30 kPa, 40 kPa, 50 kPa, 60 kPa, 70 kPa, 80 kPa, 90 kPa, or 100 kPa, or may be other values ​​between 1 kPa and 100 kPa.

[0131] Specifically, the partial pressure of the hydrogen gas is 50 kPa to 1000 kPa. For example, the partial pressure of hydrogen gas may be 50 kPa, 55 kPa, 60 kPa, 65 kPa, 70 kPa, 80 kPa, 90 kPa, 100 kPa, 200 kPa, 300 kPa, 400 kPa, 500 kPa, 600 kPa, 700 kPa, 800 kPa, 900 kPa, or 1000 kPa, or may be other values ​​between 50 kPa and 1000 kPa.

[0132] Specifically, the partial pressure of the inert gas is 1 kPa to 1000 kPa. For example, the partial pressure of the inert gas may be 1 kPa, 2 kPa, 5 kPa, 10 kPa, 20 kPa, 25 kPa, 30 kPa, 50 kPa, 100 kPa, 200 kPa, 300 kPa, 400 kPa, 500 kPa, 600 kPa, 700 kPa, 800 kPa, 900 kPa, or 1000 kPa, or may be another value between 1 kPa and 1000 kPa.

[0133] Specifically, for example, when the total pressure of the reaction system is 100 kPa, the partial pressure of the gaseous Si source can be set to 1 kPa, the partial pressure of the hydrogen gas to 50 kPa, and the partial pressure of the inert gas to 49 kPa. Alternatively, when the total pressure of the reaction system is 500 kPa, the partial pressure of the gaseous Si source can be 50 kPa, the partial pressure of the hydrogen gas can be 250 kPa, and the partial pressure of the inert gas can be 200 kPa. Alternatively, when the total pressure of the reaction system is 1500 kPa, the partial pressure of the gaseous Si source can be 100 kPa, the partial pressure of the hydrogen gas can be 1000 kPa, and the partial pressure of the inert gas can be 400 kPa. Alternatively, when the total pressure of the reaction system is 2000 kPa, the partial pressure of the gaseous Si source can be 100 kPa, the partial pressure of the hydrogen gas can be 900 kPa, and the partial pressure of the inert gas can be 1000 kPa.

[0134] As a specific example, the raw material of the gaseous Si source includes at least one of monosilane, disilane, monochlorosilane, dichlorosilane, trichlorosilane, and tetrachlorosilane. When the raw material of the gaseous Si source is monosilane, disilane, monochlorosilane, or dichlorosilane, it is in a gaseous state at room temperature, and when the raw material of the gaseous Si source is trichlorosilane or tetrachlorosilane, it is in a liquid state at room temperature, and the liquid Si source vaporizes during the pyrolysis process to become a gaseous Si source.

[0135] As a specific example, the inert gas includes at least one of nitrogen gas, helium gas, neon gas, and argon gas. Specifically, the flow rate of the inert gas is 0.2 L / min to 50 L / min. The flow rate of the inert gas is, for example, 0.2 L / min, 2 L / min, 5 L / min, 10 L / min, 15 L / min, 20 L / min, 25 L / min, 30 L / min, 35 L / min, 40 L / min, 45 L / min, or 50 L / min. The flow rate of the inert gas may be other values ​​between 0.2 L / min and 50 L / min.

[0136] Specifically, the flow rate ratio of the gaseous Si source to the inert gas is 1:1-20. For example, the flow ratio of the gaseous Si source to the inert gas is 1:1, or 1:3, or 1:6, or 1:9, or 1:12, or 1:15, or 1:18, or 1:20. It is understood that the flow ratio of the gaseous Si source to the inert gas may be other values ​​between 1:1-20. It is considered that the produced composite negative electrode material is sufficient for uniformly distributing Si in the porous carbon if the flow rate ratio of the gaseous Si source to the inert gas is 1:1. Furthermore, if the flow rate ratio of the gaseous Si source to the inert gas is 1:20 or more, the gaseous Si source can be gently dispersed in the CVI reaction gas, and the deposition rate does not decrease significantly.

[0137] Step S200 involves coating the precursor in a protective atmosphere to form a coating layer on the surface of the precursor to obtain a composite negative electrode material.

[0138] Here, the composite negative electrode material has micropores and mesopores, and the ratio of the pore volume of the micropores to the pore volume of the mesopores is (2-50):(50-98).

[0139] The oil absorption value of the above composite negative electrode material is smaller than the oil absorption value of the composite negative electrode material after the Si particles have been removed, and the difference therebetween is ≧10% when the oil absorption value of the composite negative electrode material after the Si particles have been removed is taken as 100%.

[0140] In one embodiment, the coating process includes mixing the precursor with a carbon source and controlling the pyrolysis of the carbon source in a protective atmosphere to form a carbon coating layer on the surface of the precursor.

[0141] Specifically, the pyrolysis temperature is 600°C to 1200°C. The temperature of pyrolysis is 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C. The pyrolysis temperature may also be other values ​​between 600°C and 1200°C.

[0142] Specifically, the temperature rise rate for pyrolysis is 0.1° C. / min to 50° C. / min. The heating rate for pyrolysis is 0.1°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min, 45°C / min or 50°C / min. The temperature rise rate for pyrolysis may be any other value between 0.1° C. / min and 50° C. / min.

[0143] Specifically, the protective atmosphere includes at least one of nitrogen, argon, helium, neon, krypton, and xenon.

[0144] Specifically, the gas flow rate of the protective atmosphere is 20 mL / min to 1000 mL / min. For example, the gas flow rate of the protective atmosphere may be 20 mL / min, 50 mL / min, 100 mL / min, 150 mL / min, 200 mL / min, 250 mL / min, 300 mL / min, 350 mL / min, 400 mL / min, 450 mL / min, 500 mL / min, 550 mL / min, 600 mL / min, 650 mL / min, 700 mL / min, 750 mL / min, 800 mL / min, 850 mL / min, 900 mL / min, 950 mL / min or 1000 mL / min. The gas flow rate of the protective atmosphere may be other values ​​between 20 mL / min and 1000 mL / min.

[0145] Furthermore, the method for forming the carbon coating layer includes at least one of a gas phase carbon coating process, a solid phase carbon coating process, and a liquid phase carbon coating process.

[0146] In one specific example, the carbon source includes a gas phase carbon source. Additionally, the carbon source includes a gas phase hydrocarbon-based carbon source. Additionally, the carbon source includes at least one of methane, acetylene, ethylene, ethane, propane, propylene, propyne, acetone, and benzene. In carrying out the coating process, a gaseous carbon source is introduced in a protective atmosphere and mixed with the solid composite. When the carbon source pyrolyzes, amorphous carbon deposits on the surface of the precursor to provide a carbon coating. When the carbon source comprises a gas phase carbon source, the coating process is carried out in a rotary kiln or a box kiln.

[0147] In another embodiment, the carbon source comprises a solid phase carbon source. Carbon sources also include solid phase organic carbon sources. Additionally, the carbon source includes at least one of citric acid, glucose, pitch, phenolic resin, and furfural resin. When the carbon source comprises a solid phase carbon source, the coating process is carried out in a rotary kiln, a box kiln, a roller hearth kiln, a tunnel kiln or a pusher kiln. When the carbon source includes a solid-phase carbon source, the precursor and the carbon source can be mixed by VC mixing, fusion, ball milling, suction filtration, heating under reflux, three-dimensional mixing, fluidized bed mixing, or the like.

[0148] In another embodiment, the carbon source comprises a liquid phase carbon source. Carbon sources also include liquid phase organic carbon sources. Further, the carbon source includes at least one of n-hexane, toluene, benzene, xylene, methanol, ethanol, propanol, butanol, pentanol, acetone, butanone, 2-pentanone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and pentyl acetate. When a liquid phase carbon source is used, the flow rate of the liquid phase carbon source is 1 mL / min to 200 mL / min. The flow rate of the liquid phase carbon source is, for example, 1 mL / min, 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min, 100 mL / min, 150 mL / min, or 200 mL / min. The flow rate of the liquid-phase carbon source may be any other value between 1 mL / min and 200 mL / min. When the carbon source comprises a liquid phase carbon source, the coating process is carried out in a rotary kiln, a box kiln, a roller hearth kiln, a tunnel kiln, or a pusher kiln. When the carbon source includes a liquid phase carbon source, the precursor and the carbon source can be mixed by VC mixing, fusion, ball milling, suction filtration, heating under reflux, three-dimensional mixing, fluidized bed mixing, or the like.

[0149] According to yet another embodiment of the present application, there is provided a negative electrode sheet comprising the above composite negative electrode material.

[0150] According to yet another embodiment of the present application, there is provided a battery including the above negative electrode sheet.

[0151] According to yet another embodiment of the present application, there is provided an electrical device comprising the battery described above.

[0152] The parameters in this application can be measured using the following devices and methods.

[0153] (1) True density test: Using Archimedes' principle of gas displacement (density = mass / volume) and Boyle's law (PV = nRT) under certain conditions using an inert gas with a small molecular diameter, the true volume of the test material was accurately measured and its true density was obtained. The instrument used was an Anton Paar PentaPyc 5200e true density meter.

[0154] (2) Oil absorption test: A certain mass of powder sample was placed in a mixing chamber, and oil (linseed oil or DBP-butyl phthalate) was dripped onto the sample at a constant rate and simultaneously stirred with a rotating blade at a constant rotation speed. As the sample absorbs increasing amounts of oil, the mixture changes from a free-flowing state to a semi-plastic agglomerate, and in the process the viscosity of the mixture gradually increases and a peak appears. The amount of oil dropped at 70% of the maximum torque obtained at the end point from the torque curve due to the change in viscosity characteristics was measured, and the oil absorption value (mL / 100 g) of the sample was calculated. The equipment used was an S-500 oil absorption tester made by ASAHISOUKEN, Japan.

[0155] (3) Silicon particle removal method: Approximately 0.5 g of a composite negative electrode material sample was weighed and placed in a platinum crucible and dissolved in HNO 3 A mixed acid consisting of 5 mL of HF and 10 mL of HF was added to stabilize the reaction between the mixed acid and the sample, and then the platinum crucible was placed on a hot plate at 350°C and heated to remove the acid until the hydrofluoric acid volatilized and no white smoke was emitted. Then, after cooling the crucible, another 6 mL of HCl is added and heated until the residue is completely dissolved, and what remains is the composite negative electrode material after removing the silicon particles.

[0156] (4) Measure D50 using a laser granulometer. The volume-based distribution is D 10 The diameter corresponding to a cumulative frequency of 50% is D 50 The diameter corresponding to a cumulative frequency of 90% is D 90 It is.

[0157] (5) The specific surface area is measured using a TriStar 3000 specific surface area and pore size analyzer manufactured by Micromeritics, Inc., USA.

[0158] (6) Micropore and mesopore analysis was performed using a Micromeritics ASAP2460. At the temperature of liquid nitrogen, the equilibrium adsorption amount of nitrogen gas on the surface of an object is correlated with its properties such as pore size, and the pore size can be calculated by applying multiple models in accordance with the rules for how the adsorption amount changes with relative pressure during the adsorption process. The software reports pore size distribution, total pore volume, and pore volume within a certain range using density functional theory (abbreviated as DFT).

[0159] (7) XRD peaks were measured using a PANalytical X'pertPro X-ray diffractometer, and the grain size of the Si crystal grains was obtained by fitting the Si peaks in the XRD using the software Jade 6.5.

[0160] (8) 29 SiMASNMR standard silicon structure chemical shifts 29 SiMASNMR( 29 The Si Magic Angle Spinning Nuclear Magnetic Resonance Spectroscopy (SiMAG) is a nuclear magnetic resonance spectrometer with the model number Bruker AV300. For quantitative analysis, a monopulse is used in the testing process rather than a cross-polarization method. The pulse width was 4.5 ut, θ was 54.7°, the relaxation delay (i.e., the time delay between two samplings) was 5 seconds, and the rotation speed was 7 kHz. TMS was used as a chemical shift standard.

[0161] (9) FIB-TEM specimens were prepared using the “lift-out method”: using a focused ion-electron dual-beam electron microscope with model number FEI Helios G4CX, a layer of Pt was first deposited (first electron beam deposition, then ion beam deposition) on the surface preparation site to serve as a protection layer. After that, one side of the Pt deposition film is etched into a cross section, and then the other side is etched into a cross section in the same manner. The sample stage is rotated 45°, the bottom is cut off and returned to the original position, the film is thinned to the required dimension of about 0.2 μm, both ends of the film are cut off, and the sample is taken out using a special pick-up system (a glass rod with a tip of 0.2 μm to 0.5 μm is brought close to the sample under the control of a microrobot arm. An electrostatic action is generated between the sample and the tip of the glass rod, and the sample is attracted to the tip of the glass rod. The sample is then placed on a copper mesh with collodion to obtain a TEM sample. For TEM, a Thermo Fisher SpectraS / TEM scanning transmission electron microscope was used.

[0162] (10) EDS line scan: The electron beam was traced along the surface of the sample in a selected straight line, resulting in a line scan analysis of elemental concentrations. A straight line is drawn arbitrarily from one end of the sample surface to the other end on the cross-sectional image of the sample, and the electron beam is scanned along that line to collect X-rays characteristic of the elements Si and C. The changes in these count values ​​are displayed as a graph on the phosphor screen, with the height of the graph reflecting the changes in the concentrations of the corresponding elements along the scan line. Here, the maximum value I (Intensities) along the Si scan line max Value A 1 , the lowest value I(Intensities) along the Si scan line min Value B 1 , median I(Intensities) along the Si scan line med Change the value to C 1 , C is the maximum value along the scan line I (Intensities) max Value A 2 , C the minimum value along the scan line I (Intensities) min Value B 2 , C Median along the scan line intensity I (Intensities) med Change the value to C 2 It stipulates that: The type of EDS spectrometer used was a Thermo Fisher NORAN System 7 seventh generation X-ray spectrometer.

[0163] (11) Measurement of nanoparticle size using a scanning electron microscope (SEM): A cut surface of the composite negative electrode material is prepared and an SEM photograph of the cut surface is saved. Run the software NanoMeasurer, open the SEM photograph of the statistically required cut section, set the scale and drag the mouse to display the particles on the SEM map and obtain their particle size. Five regions of 100m x 75m were randomly selected, and 20 nano-Si particles were randomly selected from each region to perform particle size statistics and obtain the particle size distribution range. The obtained particle size values ​​were subjected to normal distribution fitting using the software Origin to determine the average value and standard deviation, and the standard deviation σ was found to be ≦0.2.

[0164] (12) Measurement of silicon content by gravimetric method: 0.05g using a box atmosphere furnace 2 The sample is fired in a sintering atmosphere, causing the Si in the sample to react and become SiO, and the C is burned and produces CO. 2 The resulting powder is discharged and the Si content is weighed.

[0165] The present application will be described in detail below with reference to specific examples and comparative examples.

[0166] Example 1 The material was selected based on the porous carbon D used in this example. 50 The average pore size was 7 μm, the average pore diameter was 1.9 nm, and the average distance between pores was 1.6 nm.

[0167] 1000g of porous carbon was placed in a CVI reactor, 200℃ silane was injected into the CVI reactor at 0.5L / min, and 250℃ hydrogen gas and 250℃ high purity nitrogen gas were simultaneously injected at rates of 50L / min and 4.0L / min, respectively, to thoroughly mix the gases to obtain a gas mixture. The gas mixture was heated to about 400℃, and the turbulent gas mixture remained in the CVI reactor for 8 hours, with the total flow rate of the gas mixture being 54.5L / min. It was then allowed to cool to room temperature to obtain a precursor.

[0168] Using methane as the carbon source, the precursor was placed in a rotary kiln for vapor-phase coating, and carbonized at 900°C with methane gas and nitrogen gas as the protective atmosphere to obtain a composite negative electrode material with an amorphous carbon coating layer.

[0169] Example 2 The material was selected based on the porous carbon D used in this example. 50 The average pore size was 12 μm, the average pore diameter was 300 nm, and the average distance between pores was 90 nm.

[0170] 1000g of porous carbon was placed in a CVI reactor, 200℃ silane was injected into the CVI reactor at 1.0L / min, and at the same time, 250℃ hydrogen gas and 250℃ high purity argon gas were simultaneously injected at rates of 79L / min and 20L / min, respectively, to thoroughly mix the gases to obtain a gas mixture. The gas mixture was heated to about 400℃, and the turbulent gas mixture remained in the CVI reactor for 10h, with the total flow rate of the gas mixture being 100L / min. It was then allowed to cool to room temperature to obtain a precursor.

[0171] Low-temperature liquid-phase asphalt was used as the carbon source. The precursor and low-temperature liquid-phase asphalt were thoroughly mixed and placed in a rotary kiln for gas-phase coating. Methane gas was passed through the mixture, and the mixture was carbonized at 800°C using nitrogen gas as a protective atmosphere. The mixture was then placed in a furnace and heat-treated at 980°C for 24 hours to obtain a composite negative electrode material with an amorphous carbon coating layer.

[0172] Example 3 The material was selected based on the porous carbon D used in this example.50 The average pore size was 20 μm, the average pore diameter was 120 nm, and the average distance between pores was 70 nm.

[0173] 1000g of porous carbon was placed in a CVI reactor, 200℃ silane was injected into the CVI reactor at 0.2L / min, and simultaneously 250℃ hydrogen gas and 250℃ high purity helium gas were injected at rates of 150L / min and 2.0L / min, respectively, to thoroughly mix the gases to obtain a gas mixture. The gas mixture was heated to about 400℃, and the turbulent gas mixture remained in the CVI reactor for 4h, with the total flow rate of the gas mixture being 152.2L / min. It was then allowed to cool to room temperature to obtain a precursor.

[0174] Glucose was used as the carbon source. The precursor and glucose were thoroughly mixed and placed in a roller hearth kiln, where they were carbonized at 980°C using argon gas as a protective atmosphere, and then placed in a furnace and heat-treated at 1000°C for 18 hours to obtain a composite negative electrode material.

[0175] Example 4 The procedure was basically the same as in Example 1, except that the silane rate was 0.4 L / min and the residence time was 6 hours.

[0176] Example 5 The procedure is basically the same as in Example 1, with the difference being that when preparing the precursor, 1000g of porous carbon is placed in the CVI reactor, 900°C silane is injected into the CVI reactor at 0.5L / min, and at the same time, 950°C hydrogen gas and 950°C high-purity nitrogen gas are simultaneously injected at rates of 50L / min and 4.0L / min, respectively, to thoroughly mix the gases to obtain a gas mixture, the gas mixture is heated to about 1000°C, the turbulent gas mixture remains in the CVI reactor for 8 hours, the total flow rate of the gas mixture is 54.5L / min, and then it is cooled to room temperature to obtain the precursor.

[0177] Example 6 The procedure is basically the same as in Example 1, with the difference being that 200°C silane is injected into the CVI reactor at 1 L / min, and at the same time, 250°C hydrogen gas and 250°C high-purity nitrogen gas are simultaneously injected at rates of 50 L / min and 0.5 L / min, respectively, to thoroughly mix the gases to obtain a gas mixture, which is then heated to about 400°C, the turbulent gas mixture is allowed to remain in the CVI reactor for 8 hours, and the total flow rate of the gas mixture is 51.5 L / min.

[0178] Comparative Example 1 The procedure was basically the same as in Example 1, except that when preparing the precursor, the rate of hydrogen gas injected into the CVI reactor was 5.0 L / min, the rate of high-purity nitrogen gas injected into the CVI reactor was 4.0 L / min, the total flow rate of the gas mixture was 9.5 L / min, and the gas mixture ventilated into the CVI reactor was not in a turbulent state.

[0179] Comparative Example 2 The process is basically the same as in Example 1, with the difference being that when preparing the precursor, 1000g of porous carbon is placed in the CVI reactor, 200°C silane is injected into the CVI reactor at 2L / min, and at the same time, 250°C hydrogen gas and 250°C high-purity nitrogen gas are simultaneously injected at rates of 120L / min and 100L / min, respectively, to thoroughly mix the gases to obtain a gas mixture, the gas mixture is heated to about 400°C, the turbulent gas mixture remains in the CVI reactor for 30h, the total flow rate of the gas mixture is 222L / min, and then it is cooled to room temperature.

[0180] Comparative Example 3 The procedure is basically the same as in Example 1, with the difference being that when preparing the precursor, Si having a D50 of 3 μm to 10 μm and anhydrous ethanol were uniformly mixed in a mass ratio of 1:10, and a Si slurry having a particle size D50 of 100 nm was obtained by a ball mill method. The Si slurry and porous carbon were then uniformly mixed in a mass ratio of 10:1, and then spray granulation was performed to obtain the precursor.

[0181] Comparative Example 4 This is basically the same as in Example 1, except that the precursor was not subjected to a carbon coating treatment.

[0182] Comparative Example 5 This is basically the same as in Example 1, except that the average pore size of the porous carbon is 1200 nm, and the average distance between pores is 1000 nm.

[0183] Comparative Example 6 The procedure is basically the same as in Example 1, with the difference being that 200°C silane is injected into the CVI reactor at 0.1 L / min, and at the same time, 250°C hydrogen gas and 250°C high-purity nitrogen gas are simultaneously injected at rates of 50 L / min and 4.0 L / min, respectively, to thoroughly mix the gases to obtain a gas mixture, which is then heated to about 400°C, the turbulent gas mixture remains in the CVI reactor for 8 hours, and the total flow rate of the gas mixture is 54.1 L / min.

[0184] (Electrochemical Test) For the lithium ion batteries made of the composite negative electrode materials in Examples 1 to 4 and Comparative Examples 1 to 8, tests were performed on the initial discharge specific capacity, the initial coulombic efficiency, the capacity retention rate after 50 weeks of cycling, and the thickness expansion rate of the electrode sheet after 50 weeks of cycling.

[0185] The test method for the initial discharge specific capacity and initial coulombic efficiency was as follows: a negative electrode slurry was prepared from the composite negative electrode material, conductive carbon black, and PAA glue in a mass ratio of 75:15:10, and the slurry was applied onto copper foil and dried to produce a negative electrode sheet. The coin cell battery is assembled in an argon-filled glove box using a lithium metal sheet as the counter electrode. A charge-discharge test was performed on the button battery at a current density of 0.1C in the charge-discharge range of 0.01V to 1.5V, and the initial discharge specific capacity and initial coulombic efficiency of the button battery were obtained.

[0186] The capacity retention rate after 50 weeks of cycling and the thickness expansion rate of the electrode sheet after 50 weeks of cycling were tested by preparing a negative electrode slurry with a mass ratio of Super-P:KS-6:CMC:SBR = 92:2:2:2:2, applying it to copper foil and drying it to produce a negative electrode sheet. The coin cell battery is assembled in an argon-filled glove box using a lithium metal sheet as the counter electrode. The button battery was subjected to a 50-week charge-discharge test at a current density of 1C and a charge-discharge range of 0.01V to 1.5V, and the capacity retention rate and thickness expansion rate of the electrode sheet after 50 weeks of cycling were obtained.

[0187] [Table 1]

[0188] [Table 2]

[0189] The results shown in Tables 1-2 indicate that the composite negative electrode material prepared in Example 2 had the best overall performance.

[0190] Comparing Example 1 and Example 5, the composite negative electrode material of Example 1 has relatively high initial discharge specific capacity, initial Coulombic efficiency, and capacity retention rate after 50 weeks of cycling, and the thickness expansion rate of the electrode sheet after 50 weeks of cycling is low. This is because, when the precursor is prepared in Example 1, the temperatures of silane, hydrogen, high-purity nitrogen, and the gas mixture are appropriate, which suppresses the formation of crystalline Si, and the crystalline Si exhibits expansion anisotropy during the charge and discharge process. Therefore, the composite negative electrode material prepared in Example 1 has a more stable structure and better electrochemical performance.

[0191] Comparing Example 1 and Example 6, the proportion of the micropore volume in the pore volume ratio of the micropores to the mesopores in the composite negative electrode material prepared in Example 6 is relatively large. The composite negative electrode material prepared in Example 6 is slightly lower in the capacity retention rate after 50 weeks of cycles, the initial discharge specific capacity, and the initial coulombic efficiency than those of Example 1, and therefore the ratio of the pore volume of the micropores to the pore volume of the mesopores in the composite negative electrode material is preferably (5-23):(77-95).

[0192] The particle sizes of the Si particles in the composite negative electrode materials produced in Example 1 and Comparative Examples 1 and 2 are measured using an SEM and NanoMeasurer software. In the composite negative electrode material of Example 1, the particle diameter of all the Si particles is less than 100 nm, and the particle diameter of 70% of the particles is 50 nm to 80 nm. In contrast, the Si particles formed in Comparative Example 1 had a large particle size, with 70% of the particles having a particle size of 80 nm to 150 nm, while in Comparative Example 2, the number of Si particles in the composite negative electrode material was small and some of the particles had a large particle size. In addition, the composite negative electrode materials prepared in Comparative Examples 1 and 2 had a lower capacity retention rate after 50 weeks of cycling than that of Example 1, and the composite negative electrode material prepared in Comparative Example 2 had a lower ICE than that of Example 1 due to the small number of Si particles. It has been shown that when preparing the precursor by CVI technique, the process conditions have a significant effect on the structure and electrochemical performance of the composite anode material.

[0193] Comparing Example 1 with Comparative Example 3, the composite negative electrode material of Example 1 had significantly higher capacity retention rate after ICE and 50-week cycles than Comparative Example 3, and the thickness expansion rate of the electrode sheet after 50-week cycles was significantly lower than that of Comparative Example 3. This is because in the precursor of Example 1, Si atoms are uniformly embedded in the porous carbon at the atomic level, which corresponds to a porous carbon material that has been modified by bulk phase doping. The Si atoms can form amorphous Si-C bonds with C atoms, and the volume expansion during the lithium desorption process is small and the lithium ion conductivity is high, improving the cycle performance of the material.

[0194] Comparing Example 1 and Comparative Example 4, the precursor of Comparative Example 4 was not subjected to carbon coating treatment, and the capacity retention rate after 50 weeks of cycling and the thickness expansion rate of the electrode sheet after 50 weeks of cycling of the composite negative electrode material of Example 1 were both better than those of Comparative Example 4, indicating that the carbon coating layer on the surface of the precursor improves the conductivity of the entire material. The carbon coating layer can avoid direct contact with the Si particles, which may expose the electrolyte, and improve the cycle performance.

[0195] Comparing Example 1 and Comparative Example 5, the composite negative electrode material of Comparative Example 5 has a high silicon content. Although the initial discharge specific capacity of the material is high, the capacity retention rate after 50 weeks of cycling is low, and the thickness expansion rate of the electrode sheet after 50 weeks of cycling is high. This is because the porous carbon used in Comparative Example 5 had a large average pore size and an average distance between the pores, and when Si penetrated into the porous carbon by CVI technology, the Si and the C in the porous carbon could not be mixed uniformly at the nano level. The uneven distribution of Si and C led to a decrease in the electrochemical performance of Comparative Example 5, and the pores in the porous carbon of Comparative Example 5 were not sufficiently developed, resulting in a small amount of Si particles being deposited on the porous carbon.

[0196] The composite negative electrode materials produced in Example 1 and Comparative Example 6 differ greatly in the ratio of the volume of pores to mesopores. The pore volume of the mesopores in the composite negative electrode material prepared in Comparative Example 6 is higher than that in Example 1 because the inflow rate of silane during the deposition process in Comparative Example 6 was low, resulting in insufficient silicon being deposited in the pores of the porous carbon, which in turn resulted in a significant decrease in the initial discharge specific capacity of the material, and therefore a high pore volume of the mesopores in the final negative electrode material.

[0197] The present application demonstrates that by rationally designing the ratio of the pore volume of micropores to the pore volume of mesopores, the stability of the composite negative electrode material can be effectively improved, and its cycle performance can be further improved, while the initial discharge specific capacity and initial coulombic efficiency can be significantly improved.

[0198] The technical features of the above-described embodiments may be combined in any combination. For the sake of brevity, not all possible combinations of the individual technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as being within the scope of the description of this specification.

[0199] The above-mentioned examples merely illustrate some embodiments of the present application, and the description has been specifically detailed, but therefore should not be construed as limiting the scope of the claims of the application. Furthermore, those skilled in the art can make some modifications and improvements without departing from the concept of the present application, which are within the scope of the claims of the present application. Therefore, the scope of protection of this application should be according to the claims.

Claims

1. A composite negative electrode material comprising a core containing a porous carbon material and Si particles, and a coating layer located on at least a portion of a surface of the core, the Si particles are distributed on at least one of a surface and inside pores of the porous carbon material, the composite negative electrode material has micropores and mesopores; the ratio of the pore volume of the micropores to the pore volume of the mesopores is from 2:98 to 50:50; The composite negative electrode material has an oil absorption value smaller than an oil absorption value of the composite negative electrode material after the Si particles have been removed, and the difference therebetween is ≧10% when the oil absorption value of the composite negative electrode material after the Si particles have been removed is taken as 100%.

2. A composite negative electrode material comprising at least one of the following features (1) to (17): (1) In the FIB-TEM test of the composite negative electrode material, the EDS scanning line density is 0.90≦(A 1 -C 1 ) / (C 1 -B 1 )≦1.10, and |((A 1 -B 1 ) / 2C 1 ) 2 −1|≦0.01, where A 1 is the maximum value along the scan line concentration of Si, and B 1 is the minimum value along the scan line concentration of Si, and C 1 is the median value along the scan line concentration of Si, (2) In the FIB-TEM test of the composite negative electrode material, the EDS scanning line density is 0.90≦(A 2 -C 2 ) / (C 2 -B 2 )≦1.10, and |((A 2 -B 2 ) / 2C 2 ) 2 −1|≦0.01, where A 2 is the maximum value along the C scan line density, and B 2 is the minimum value along the C scan line density, and C 2 is the median value along the C scan line density, (3) The composite negative electrode material 29 In the Si-NMR spectrum, the Si-C resonance peak is between -10 ppm and 20 ppm, and its intensity is D 1 The Si resonance peak is between -90 ppm and -110 ppm, and its intensity is D 2 In the case where D 2 / D 1 ≧10, (4) The composite negative electrode material contains amorphous Si—C bonds; (5) The X-ray diffraction pattern of the composite negative electrode material includes a SiC crystal peak; (6) The porosity of the composite negative electrode material is 10% to 20%; (7) is that when the composite negative electrode material is lithiated to 50% of its theoretical lithiation capacity, the porosity A1 of the electrode sheet containing the composite negative electrode material satisfies A1 ≧ 30%; (8) is that when the composite negative electrode material is lithiated to 70% of its theoretical lithiation capacity, the porosity A2 of the electrode sheet containing the composite negative electrode material satisfies 20%≦A2<30%; (9) is that when the composite negative electrode material is lithiated to 80% of its theoretical lithiation capacity, the porosity A3 of the electrode sheet containing the composite negative electrode material satisfies 10%≦A3<20%; (10) A ratio of the pore volume of the micropores to the pore volume of the mesopores is from 5:95 to 23:77; (11) After complete lithium intercalation, the average pore size of the closed pores of the composite negative electrode material is 0-10 nm; (12) The mass percentage of Si in the composite negative electrode material is 10% to 90%; (13) The specific surface area of ​​the composite negative electrode material is 0.5 m 2 / g to 50m 2 / g, (14) The true density of the composite negative electrode material is 1.80 g / cm 3 ~2.90g / cm 3 It is to be (15) The average particle size of the composite negative electrode material is 1 μm to 25 μm; (16) The average thickness of the coating layer is 1 nm to 100 nm; 17. The composite negative electrode material of claim 1, wherein the coating layer comprises a carbon coating layer.

3. A composite negative electrode material comprising at least one of the following features (1) to (9): (1) The average pore size of the porous carbon is R1, and the value of R1 is in the range of 0.2 nm to 1000 nm; (2) The ratio of the pore volume of the porous carbon having a diameter of 2 nm to 100 nm to the total pore volume is 50% or more; (3) In the porous carbon, a ratio of a pore volume of the micropores to a pore volume of the mesopores is from 95:5 to 50:50; (4) The average distance between the pores of the porous carbon is H1, and the value of H1 ranges from 1 nm to 500 nm; (5) The average distance H1 between the pores of the porous carbon is equal to or less than the average pore diameter R1 of the porous carbon; (6) The particle size of the porous carbon is 1 μm to 50 μm; (7) The Si particles in the composite negative electrode material contain amorphous silicon and have a particle size in the range of 1 to 110 nm; (8) The average pore size of the Si particles in the composite negative electrode material is 1 nm to 200 nm; (9) The composite negative electrode material according to claim 1 or 2, characterized in that the grain size of the Si crystal grain of the composite negative electrode material is 2 nm to 10 nm, and the standard deviation σ≦0.

2.

4. depositing Si particles on the surface and / or within the pores of the porous carbon using a chemical vapor infiltration process to obtain a precursor; and A method for preparing a composite negative electrode material, comprising: coating the precursor in a protective atmosphere to form a coating layer on the surface of the precursor to obtain a composite negative electrode material, the composite negative electrode material comprises micropores and mesopores, and the ratio of the pore volume of the micropores to the pore volume of the mesopores is from 2:98 to 50:50; The method for preparing a composite negative electrode material, wherein the oil absorption value of the composite negative electrode material is smaller than the oil absorption value of the composite negative electrode material after the Si particles have been removed, and the difference therebetween is ≧10% when the oil absorption value of the composite negative electrode material after the Si particles have been removed is taken as 100%.

5. The step of depositing Si particles on at least one of the surface and pores of the porous carbon using the chemical vapor infiltration process includes the steps of supplying porous carbon, flowing a reactive gas, and pyrolyzing the reactive gas to deposit Si particles on at least one of the surface and pores of the porous carbon, and includes at least one of the following features (1) to (9): (1) is that the reaction gas contains a gaseous Si source, hydrogen gas, and an inert gas; (2) The temperature of the pyrolysis is 300° C. to 500° C.; (3) The time of the pyrolysis is 0.2 h to 20 h; (4) The flow rate of the reaction gas is 50 L / min to 200 L / min; (5) The reaction gas comprises a gaseous Si source, and the raw material of the gaseous Si source includes at least one of monosilane, disilane, monochlorosilane, dichlorosilane, trichlorosilane, and tetrachlorosilane; (6) The reaction gas comprises an inert gas, and the inert gas includes at least one of nitrogen gas, helium gas, neon gas, and argon gas; (7) The reaction gas comprises an inert gas, and the flow rate of the inert gas is 0.2 L / min to 50 L / min; (8) The flow rate ratio of the gaseous Si source to the inert gas is 1:1 to 20; (9) The method for preparing the composite negative electrode material according to claim 4, characterized in that the method for preparing the porous carbon includes a step of pyrolyzing an organic carbon source and a step of chemically activating the organic carbon source.

6. The coating treatment includes a step of mixing the precursor with a carbon source and controlling thermal decomposition of the carbon source in a protective atmosphere to form a carbon coating layer on the surface of the precursor, and the preparation method includes at least one of the following characteristics (1) to (14): (1) The method for forming the carbon coating layer includes at least one of a gas phase carbon coating process, a solid phase carbon coating process, and a liquid phase carbon coating process; (2) The inert gas includes at least one of nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas; (3) The gas flow rate of the protective atmosphere is 20 mL / min to 1000 mL / min; (4) The carbon source comprises a gas phase carbon source; (5) The carbon source includes a gas-phase carbon source, and the gas-phase carbon source includes a gas-phase hydrocarbon-based carbon source; (6) The carbon source includes a gas phase carbon source, and the gas phase carbon source includes at least one of methane, acetylene, ethylene, ethane, propane, propylene, propyne, acetone, and benzene; (7) The carbon source comprises a solid phase carbon source; (8) The carbon source comprises a solid-phase carbon source, and the solid-phase carbon source comprises a solid-phase organic carbon source; (9) The carbon source includes a solid-phase carbon source, and the solid-phase carbon source includes at least one of citric acid, glucose, pitch, phenolic resin, and furfural resin; (10) The carbon source comprises a liquid phase carbon source; (11) The carbon source comprises a liquid phase carbon source, and the liquid phase carbon source comprises a liquid phase organic carbon source; (12) The carbon source includes a liquid phase carbon source, and the liquid phase carbon source includes at least one of n-hexane, toluene, benzene, xylene, methanol, ethanol, propanol, butanol, pentanol, acetone, butanone, 2-pentanone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and pentyl acetate; (13) The temperature of the pyrolysis is 600° C. to 1200° C.; (14) The method for preparing a composite negative electrode material according to claim 4, characterized in that the temperature rise rate of the thermal decomposition is 0.1° C. / min to 50° C. / min.

7. A preparation method comprising at least one of the following features (1) to (4): (1) The total pressure of the reaction system by the reaction gas is 100 kPa to 2000 kPa; (2) The total pressure of the reaction system by the reaction gas is 100 kPa to 2000 kPa, and the partial pressure of the gaseous Si source is 1 kPa to 100 kPa; (3) The total pressure of the reaction system by the reaction gas is 100 kPa to 2000 kPa, and the partial pressure of the hydrogen gas is 50 kPa to 1000 kPa; (4) The method for preparing a composite negative electrode material according to claim 5, characterized in that the total pressure of the reaction system by the reactive gas is 100 kPa to 2000 kPa, and the partial pressure of the inert gas is 1 kPa to 1000 kPa.

8. A negative electrode sheet comprising the composite negative electrode material according to any one of claims 1 to 3, or the composite negative electrode material prepared by the preparation method according to any one of claims 4 to 7.

9. A battery comprising the negative electrode sheet according to claim 8.

10. An electrical device comprising the battery of claim 9.

Citation Information

Patent Citations

  • Lithium-ion battery graphitized mesoporous carbon / silicon composite anode materials and preparation method thereof

    CN102456876A

  • Novel material having highly durable lithium insertion and method for manufacturing the same

    JP2018534720A

  • Electroactive Materials for Metal-Ion Batteries

    JP2022506881A

  • Negative electrode active material and lithium secondary battery including the same

    US20180219216A1

  • Carbon–silicon composite

    WO2021241749A1

Cited By

  • Negative electrode active material and method for producing the same

    JP7898003B1

  • Negative electrode active material and method for producing the same

    JP7898589B1